Activity‐dependent astrocyte swelling is mediated by pH‐regulating mechanisms. Issue 10 (26th July 2017) - Larsen, Brian Roland; MacAulay, Nanna
Abstract: During neuronal activity in the mammalian brain, the K + released into the synaptic space is initially buffered by the astrocytic compartment. In parallel, the extracellular space (ECS) shrinks, presumably due to astrocytic cell swelling. With the Na + /K + /2Cl − cotransporter and the Kir4.1/AQP4 complex not required for the astrocytic cell swelling in the hippocampus, the molecular mechanisms underlying the activity‐dependent ECS shrinkage have remained unresolved. To identify these molecular mechanisms, we employed ion‐sensitive microelectrodes to measure changes in ECS, [K + ]o and [H + ]o /pHo during electrical stimulation of rat hippocampal slices. Transporters and receptors responding directly to the K + and glutamate released into the extracellular space (the K + /Cl − cotransporter, KCC, glutamate transporters and G protein‐coupled receptors) did not modulate the extracellular space dynamics. The HCO 3 – ‐transporting mechanism, which in astrocytes mainly constitutes the electrogenic Na + / HCO 3 – cotransporter 1 (NBCe1), is activated by the K + ‐mediated depolarization of the astrocytic membrane. Inhibition of this transporter reduced the ECS shrinkage by ∼25% without affecting the K + transients, pointing to NBCe1 as a key contributor to the stimulus‐induced astrocytic cell swelling. Inhibition of the monocarboxylate cotransporters (MCT), like‐wise, reduced the ECS shrinkage by ∼25% without compromising the K + transients. Isosmotic reduction of extracellular Cl − revealed a requirement for this ion in parts of the ECS shrinkage. Taken together, the stimulus‐evoked astrocytic cell swelling does not appear to occur as a direct effect of the K + clearance, as earlier proposed, but partly via the pH‐regulating transport mechanisms activated by the K + ‐induced astrocytic depolarization and the activity‐dependent metabolism. Main Points: Activity‐evoked astrocyte cell swelling does not occur as a direct function of the clearance of synaptically released K + or glutamate. The astrocytic swelling is, instead, mediated by the pH‐regulating cotransporters of HCO 3 – and lactate.